TEACHING SPEAKING SKILLS USING TECHNOLOGY (AI, VR, OR SPEECH RECOGNITION) (Multidisciplinary Journal of Science and Technology, 2026)
The article examines how new technologies, such as virtual reality (VR), artificial intelligence (AI), and speech recognition, are changing how individuals engage with their environment. It highlights the AI is becoming more and more prevalent in daily life, from decision-making tools in healthcare and education to personalized assistants. In the meantime, voice recognition is presented as an accessibility tool that enables people with disabilities to traverse digital settings and speak more freely. The paper makes the case that although these technologies offer exciting prospects, they also bring ethical and privacy issues that need to be addressed through real-world examples and professional insights. In the end, the article portrays technology as a force influencing human connection, productivity, and society as a whole rather than only a tool.